The Role of Mosque in Islamic Da'wah: a Case Study at Al Bukhary Mosque Alor Malai, Jalan Langgar, Alor Setar, Kedah Darul Aman - Noor Azah Bt Abdul Aziz (Kolej Universiti Islam Malaysia, 2022)
This research was study on Al-Bukhary mosque located in Alor Setar Kedah with focusing on discussion about the role of Al-Bukhary mosque in its effort to bear a good person as a servant to Allah S.W.T. This research also study on the acceptance of society to Al-Bukhary mosque and the activities that was held at there whether it give the effective impact or not. To collect the information, various methods were used by writer such as observation, questionnaires, interview and refer to the sources that are suitable with the research. The result was shown that Al-Bukhary mosque was playing its role in spread of Islamic da'wah and the activity was given a positive effect to society. From the study also shown that society was, accept the mosque as an Islamic development center, generally in Kedah Darul Aman.